Effects of MCI-154 on calcium sensitivity of contractile system and calcium release from sarcoplasmic reticulum in saponin-skinned rat myocardium - Huang Yan; He Zhen-He; Li Yun-Xia (Acta Pharmacologica Sinica, 2016)
AIM: To explore the possible mechanisms underlying the positive inotropic effect of MCI-154. METHODS: Skinned fibers with disrupted or preserved sarcoplasmic reticulum (SR) were prepared by saponin 500 or 50 mg.L-1. The tension-pCa relationship and pCa50 of saponin (500 mg.L-1)-skinned fibers were taken as the indices of Ca2+ sensitivity of contractile proteins. The amplitude of caffeine-induced contracture was an index of Ca2+ release from SR in saponin (50 mg.L-1)-skinned fibers. RESULTS: 1) MCI-154 (0.1 mmol.L-1) showed a Ca2+ sensitizing effect on contractile proteins. The pCa50 was increased to 5.84 (5.54-6.14) compared with control value 5.54 (5.30-5.79) (P < 0.01, n = 8). Hill coefficient n was decreased by 0.29 (P < 0.01, n = 8); 2) No contracture was produced by MCI-154 in preparations with preserved SR. Caffeine-induced contracture before and after MCI-154 treatment were not changed (P > 0.05, n = 4). CONCLUSION: MCI-154 directly enhances the Ca2+ sensitivity of contractile protein but has little effect on Ca2+ release from SR in rat skinned cardiac fibers.